Management of hybrid powertrain dynamics and energy consumption for 2WD, 4WD, and HMMWV vehicles. (February 2017) - Raslavičius, Laurencas; Keršys, Artūras; Makaras, Rolandas
Abstract: Energy consumption for any vehicle is described by energy balance (relationship between "energy in" and "energy out"), which consists of energy produced, energy consumed, internal losses as well as the need to overcome the inertia resistance to motion. Hybrid vehicles show big potential for further reduction in fuel consumption and exhaust gas emissions. Therefore, there is nothing strange in the fact that the hybrid cars are often identified as step on the journey to a more sustainable future. Currently, the powertrain concept allows synchronization of the operation of an ICE and an electric motor and redistribution of mechanical energy flows with the help of transmission shifts depending on the mode of operation of the hybrid powertrain (HPT). Different HPT control algorithms are applied in hybrid vehicle designs, however, the purpose of all of them is to: (i) minimize fuel consumption, (ii) minimize exhaust gas emission, (iii) minimize the system price, and (iv) ensure good vehicle control characteristics. This paper presents the novel algorithms suitable for real-time estimation of economic and ecological characteristics for the hybrid 2WD, 4WD, and High Mobility Multipurpose Wheeled Vehicle (HMMWV) vehicles moving under urban, extra-urban and off-road conditions.